Dynamics of civil structures : Proceedings of the 28th IMAC, A Conference on Structural Dynamics, 2010 - International Modal Analysis Conference (28th : 2010 : Jacksonville, Fla.); Proulx, Tom (Thomas William) (New York : Springer)
Includes bibliographical references